1986
DOI: 10.1159/000124693
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Levels of Pro-opiomelanocortin-Derived Peptides in Sheep following Hypothalamo-Pituitary Disconnection

Abstract: We have studied the control of the pituitary-adrenal axis in ovariectomized sheep following hypothalamo-pituitary disconnection (HPD) by following plasma levels of immunoreactive (ir-) products of pro-opiomelanocortin (POMC). In ovariectomized HPD ewes, gonadotropin levels were below detection limits. In contrast, levels of ir-ACTH were modestly but significantly elevated over those in matched ovariectomized control ewes, though cortisol levels were not significantly different; levels of ir-αMSH and ir-βEP (β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…Both CRF and AVP have been shown to stimulate POMC peptide levels in the sheep [16], and although a negative regu latory factor has not yet been reported these data strongly sup port such a control mechanism. Our data are also supported by our previous observations [ 12] that in the OVX/HPD sheep ir-ACTH continues to be secreted from the AP in the absence of the stimulatory hypothalamic factors, and that plasma cortisol levels in OVX/HPD ewes are the same as [ 12] or slightly higher than 116] intact levels, suggesting that in the hypothalamopituitary intact sheep inhibitory hypothalamic factors exist which tonically suppress POMC mRNA levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both CRF and AVP have been shown to stimulate POMC peptide levels in the sheep [16], and although a negative regu latory factor has not yet been reported these data strongly sup port such a control mechanism. Our data are also supported by our previous observations [ 12] that in the OVX/HPD sheep ir-ACTH continues to be secreted from the AP in the absence of the stimulatory hypothalamic factors, and that plasma cortisol levels in OVX/HPD ewes are the same as [ 12] or slightly higher than 116] intact levels, suggesting that in the hypothalamopituitary intact sheep inhibitory hypothalamic factors exist which tonically suppress POMC mRNA levels.…”
Section: Discussionsupporting
confidence: 90%
“…Further evi dence for a nonhypothalamic, putatively direct effect of glu cocorticoids on the pituitary is provided in our previous study in which ovariectomized hypothalamopituitary disconnected (OVX-H PD) ewes treated with dexamethasone had lowered plasma ACTH levels compared to OVX controls [12], That study also suggested that the removal of hypothalamic input reReceived: June 20, 1988 Accepted after revision: January 18, 1989 suited in moderately elevated ACTH plasma levels. To investi gate further the direct effect of glucocorticoids, and to elucidate the contribution of hypothalamic factors to POMC gene ex pression, we have used our HPD sheep model [13] to study POMC mRNA levels in the sheep APand NIL.…”
mentioning
confidence: 96%
“…It may be assumed that the release of POMC peptides was increased in lesioned NILs, as was also reported in the hypothalamo-pituitary disconnected sheep [10]. A decrease in POMC peptide immunoreactivity in the IL was also observed after pituitary stalk transection [13] which also eliminates neural inputs to the IL.…”
supporting
confidence: 60%
“…Since it is difficult to demonstrate inhibition of basal ACTH re lease by cortisol prior to 120 days, the findings of the present study do not clarify the role of cortisol in the di rect inhibition of ACTH release in the fetal sheep. It is of interest to note that dexamethasone administered to the adult HPD sheep inhibits ir-ACTH release [18]; this may indicate that the ACTH-producing cells have different sensitivities to exogenous glucocorticoids in the adult and fetal sheep. It must be noted that differences in circulat ing concentrations of cortisol in the fetal and adult sheep may be responsible for the suggested differences in gluco corticoid sensivitity.…”
Section: Discussionmentioning
confidence: 99%